Geología de los cuadrángulos de Río Acre 22-v, Iñapari 22-x, Qda. Mala 23-v, Iberia 23-x, San Lorenzo 23-y, Puerto Lidia 24-v, Río Manuripe 24-x, Mavila 24-y, Santa María 24-z, Valencia 25-z, Palma Real 26-z y Río Heath 27-z. Hojas: SC 19-10, SC 19-14, SC 19-15, SD 19-3 y SD 19-7 – [Boletín A 123] - Romero Pittman, Lidia (1998)
199 p., 12 mapas